Israel : 2018 Article IV Consultation-Press Release and Staff Report. (IMF Staff Country Reports; Country Report, 2018)
Israel's economy is growing well with inflation remaining low and the housing market cooling. Growth of about 3 1\2 percent in 2017 helped bring unemployment below four percent in early 2018, supporting robust wage rises averaging 3u percent. Yet, partly owing to the appreciation of the shekel, inflation remained below the 1-3 percent target range. House price increases slowed to below two percent as proposed tax measures deterred investor interest. Prospects for the next few years are for growth to remain around 3 1\2 percent with inflation rising gradually.